The butterfly [videorecording (DVD)] - Muyl, Philippe; Serrault, Michel, 1928-2007; Bouanich, Claire; Dieu, Nade (First-Run Feaures, 2004)
The young daughter of a new neighbor tries to convince an elderly butterfly collector to help her track down an elusive butterfly she calls Isabelle.